Studi Literatur: Hubungan Pengetahuan dengan Stigma pada Penderita HIV/AIDS (ODHA) - Nila Alfiani; Ayik Mirayanti Mandagi; Ahmad Rido‚Äôi uda Prayogi; Dians anto Prayoga (Politeknik Kesehatan Kemenkes Mamuju, 2021)
HIV/AIDS is a disease that has become a pandemic and worries people all over the world, because until now there has not been found a vaccine or drug for the prevention of HIV/AIDS. HIV positive cases in Indonesia from year to year have increased. The problems faced by people with HIV/AIDS are very complex. Every day the patient's condition will get weaker if he does not take medication regularly because the HIV virus will attack the patient's immune system. In addition, the stigma and discrimination of the surrounding community are also a burden that must be borne by people with HIV AIDS. The stigma makes HIV sufferers worse, with this stigma, HIV sufferers are ashamed to seek treatment at a health service. This writing is to determine the relationship between knowledge and stigma against people living with HIV/AIDS (PLWHA) through a review of various literature with the same theme. The method used in this paper uses rivew literature. This type of research uses systematic review. The study design used retrospective, prospective and systematic review methods. There is a relationship between knowledge and stigma against PLWHA. People with low knowledge tend to stigmatize people with HIV.